Box- Jenkins Methodology Used in Predict The Numbers of Patients with Diabetes in DiyalaProvince - Yaqub Yousif, Haitham (International Journal of Psychosocial Rehabilitation, 2020)
The sugar disease had been known since ancient times, where a Greek physician, Aritaos, observed in early 200 BC that some patients developed symptoms of frequent urination and extreme thirst. This phenomenon has been named "policyholders" or "Aldiabats," which is a Latin word that means going to the bathroom chair." have discovered the scientists Joseph von Mereynj Oscar Menkoski In 1889, the role of the pancreas in diabetes was discovered when they removed the pancreas completely from dogs, where they showed signs and symptoms of diabetes that led to their deaths after a brief period, and in 1910, the world discovered that Sir Edward Albert Scheffer said diabetic patients suffer a shortage of a chemical produced by the pancreas called insulin. The diabetes at present from more diseases prevalent in the entire world advanced him and developed as the number of people infected with the disease increased, and because of the seriousness of this disease and how to predict the numbers of infected and build a standard form to him, it is here that the idea of this research came, which was intended to use one of the advanced methods of time series and of methodology Box-Jenkins analysis to predict the numbers of people with diabetes in Diyala province through the examination of a number of models and choose the best model among these models to represent monthly from 2009-2012 series and thus to predict until the end of 2014.